Low gH/gL (Sub)Species-Specific Antibody Levels Indicate Elephants at Risk of Fatal Elephant Endotheliotropic Herpesvirus Hemorrhagic Disease - Tabitha E. Hoornweg; Willem Schaftenaar; Victor P. M. G. Rutten; Cornelis A. M. de Haan (Viruses, 2024)
Elephant endotheliotropic herpesviruses (EEHVs), of which eleven (sub)species are currently distinguished, infect either Asian (Elephas maximus) or African elephants (Loxodonta species). While all adult elephants are latently infected with at least one EEHV (sub)species, young elephants, specifically those with low to non-detectable EEHV-specific antibody levels, may develop fatal hemorrhagic disease (EEHV-HD) upon infection. However, animals with high antibody levels against EEHV(1A) gB, an immunodominant antigen recognized by antibodies elicited against multiple (sub)species, may also occasionally succumb to EEHV-HD. To better define which animals are at risk of EEHV-HD, gB and gH/gL ELISAs were developed for each of the Asian elephant EEHV subspecies and assessed using 396 sera from 164 Asian elephants from European zoos. Antibody levels measured against gB of different (sub)species correlated strongly with one another, suggesting high cross-reactivity. Antibody levels against gH/gL of different subspecies were far less correlated and allowed differentiation between these (sub)species. Importantly, while high gB-specific antibody levels were detected in the sera of several EEHV-HD fatalities, all fatalities (n = 23) had low antibody levels against gH/gL of the subspecies causing disease. Overall, our data indicate that (sub)species-specific gH/gL ELISAs can be used to identify animals at risk of EEHV-HD when infected with a particular EEHV (sub)species.